The Effect of Digital Application Rewards on Elementary School Students' Motivation and Learning Engagement Through Digital Behaviorism - Hasan Fauzi; Novita Barokah; Ani Ani (International Journal Of Health Science, 2025)
The development of digital technology has led to the emergence of learning applications that offer rewards as a strategy to reinforce students' learning behaviors in elementary schools. This study aims to systematically examine the influence of rewards in digital learning applications on students' motivation and engagement through the principles of digital behaviorism. The method used is a Systematic Literature Review (SLR), involving identification, selection, extraction, and synthesis of articles from international and national scientific databases. The findings indicate that digital rewards, such as points, badges, leaderboards, and instant feedback, can enhance both intrinsic and extrinsic motivation, strengthen emotional, cognitive, and behavioral engagement, and promote learning consistency and independence. These findings provide practical implications for teachers in designing interactive and engaging learning experiences and serve as a reference for application developers and researchers to develop effective digital reinforcement strategies